2020
DOI: 10.9734/ajarr/2020/v10i430251
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Antibacterial Study of Co (II) and Cu (II) Complexes of Sulfamethoxazole

Abstract: Complexes of Co and Cu with SMZ were successfully synthesized (1:2 molar ratio) in good yield and characterized by using UV-vis, FTIR, melting point/decomposition temperature, electrical conductivity and solubility in different solvents of varying polarity and proticity. All the prepared complexes were coloured. From the IR results, 529, 631, 528 and 779 cm-1 bands were observed in the spectra of the complexes which were absent in the free ligand spectrum thus, showing the presence of metal-ligand bond (coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…From the literature, we did not find any biological features of nickel complexes [27][28][29][30]. Adamo et al in [31] compared the activity of SMX and the complexes of (Co(II)) and Cu(II) against S. aureus and E. coli; they found that the hazard of the activity was improved. The improved performance of the complexes is due to chelation, with the increase in lipophilic properties ultimately decreasing the polarity of the metal atom, allowing it to permeate through the bacterial membrane's lipid layers [32,33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the literature, we did not find any biological features of nickel complexes [27][28][29][30]. Adamo et al in [31] compared the activity of SMX and the complexes of (Co(II)) and Cu(II) against S. aureus and E. coli; they found that the hazard of the activity was improved. The improved performance of the complexes is due to chelation, with the increase in lipophilic properties ultimately decreasing the polarity of the metal atom, allowing it to permeate through the bacterial membrane's lipid layers [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The improved performance of the complexes is due to chelation, with the increase in lipophilic properties ultimately decreasing the polarity of the metal atom, allowing it to permeate through the bacterial membrane's lipid layers [32,33]. As a result, [Co(C 10 H 11 N 3 O 3 S)] and [Cu(C 10 H 11 N 3 O 3 S)] could be used as lead compounds for developing antibiotics against the bacteria strains studied (S. aureus and E. coli) [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation